Recognizing and Addressing the Oral Health Needs of Georgia - Carole Hanes (Journal of the Georgia Public Health Association, 2017)
Background: The intent of this report is to provide an assessment of oral health needs for Georgia and to highlight the efforts underway at the Dental College of Georgia (DCG) at Augusta University to address these needs. In underserved areas of Georgia, the burden of untreated oral disease remains high. Because of in-migration and the inadequate availability of educational programs, the population continues to grow faster than the number of health care providers. Methods: An overview of the oral health needs in Georgia is provided, along with a review of the ongoing outreach by the DCG to address those oral health needs. The data presented are derived from a variety of reports on oral health care workforce issues in Georgia between 2004 and 2014. Results: By partnering with dental clinics across the state of Georgia, the DCG continues to improve the provision of primary oral health care in underserved communities. This effort expands the clinical outreach through year-round student rotations and by fostering collaboration between dental and medical students within these clinics with the integration of primary care and public health prevention strategies. Recruitment to address the shortage and maldistribution of dentists and admissions policies to increase class size and to enhance diversity are also discussed. Conclusions: The DCG will continue to collaborate with Dental Public Health, private dental clinics, and Area Health Education Centers to treat the underserved in a network of statewide clinics. Additionally, they will provide a larger and more diverse cohort of dentists. The goal is to expand overall activities for a greater statewide impact on oral health during these difficult economic times.